Overview of the modern chinese science through the prism of the “Chinese dream” (Journal of Philosophy Culture and Political Science, 2020)
Recent events in the world and radical changes in the development of human civilization haveonce again proved the importance of the concept as “science”. The article examines how the People’sRepublic of China develops science and innovation to realize the concept of the “Chinese Dream”. Untilnow, on the world market, China’s industrial export policy has been carried out through the expansion ofits cheap goods. This strategy is no longer effective in the competition. This is due to the need for hightechproduction: the creation and development of high-quality products. The current economic growthand the current foreign economic situation, the accelerated modernization of the Chinese economy arefavorable on a modern technological basis. The introduction of a complex of high technologies in organizationsand mechanisms representing the national innovation system and industry is reflected in thesearch and updating of new products and technologies in the form of scientific knowledge.The article is based on the principle of the scientific and technological development of China in thepolitical, economic, trade, humanitarian spheres, taking place in the modern world. In addition, some issuesof Kazakh-Chinese bilateral cooperation in the field of science were analyzed. The paper were usedthe theory of “soft power” in international relations and the Chinese concept of “harmonious world”.Key words: People’s Republic of China, theoretical foundations of China’s foreign policy, “Chinesedream”, soft power.